Laporan Kasus: Dengue Fever dengan Warning sign dan Diare Akut pada Bayi - Karina Haque; Dina Aristiya Sumarno (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Introduction: Dengue fever is a viral infection transmitted through the bite of infected female Aedes aegypti mosquito, caused by four dengue virus serotypes (DEN-1 to DEN-4), with clinical manifestations ranging from asymptomatic to severe disease and may be accompanied by warning sign. Concurrent infections, such as acute diarrhea, may worsen outcomes, particularly in children. Case Report: A nine-month-old female presented with a five-day history of intermittent fever and watery diarrhea. Additional symptoms included vomiting, lethargy, and decreased appetite. Physical examination showed a moderately ill appearance and sunken eyes. Laboratory findings revealed positive dengue IgM, negative dengue IgG, thrombocytopenia (22,000/µL), and hematocrit of 37%. The patient was diagnosed with dengue fever with warning sign and acute diarrhea. Management included intravenous crystalloid fluids, antipyretics, antibiotics, H2 receptor antagonists, and zinc supplementation. Conclusion: Dengue with warning sign and concurrent acute diarrhea in children increases the risk of morbidity and mortality. Early and appropriate management is essential to prevent disease progression and improve clinical outcomes.